Complex Motor Stereotypies in Non-Autistic, Non-Retarded Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The records of 40 children (63% male) aged 9 months to 17 years with complex motor stereotypies seen between 1993 and 2003 were reviewed at the Kennedy Krieger Institute. Johns Hopkins University School of Medicine, Baltimore, MD.